Architectural Monuments During The Mughals Rule - Pangging, Jeoti (International Journal of Advanced Science and Technology, 2020)
There was an incomparable architectural activity in India under the Mughals rule. The traditions in the field of architecture, painting, literature and music created pleasure during this period. The Mughal emperors were keen lovers of nature and art and their personality was, to a certain extent, reflected in the art and culture of their time. Under their patronage, all arts particularly architecture, painting and music made special progress and all kinds of artists used to received encouragement from the state. The Mughal emperors were great builders. So, the Mughal period it regarded as the ‘Golden Age of Architecture’ in the Indian history. The Mughals, their empire, their warriors and their affairs, both of love and war, no longer exist, but their buildings that tell even today to story of their capability and personality, have immortalized them for all times. We can imagine how great builders the Mughals have been by seeing their buildings that are found even to this day. The objectives development under the Mughal Empire.